Class II malocclusion with deep overbite: a sequential approach - Martinelli,Fernando Lima (2012)
OBJECTIVE: The aim of this case report was to evaluate the results of deep overbite correction by the segmented arch technique. METHODS: The first stage of the treatment was performed with this technique to intrude incisors and canines. A maxillary transpalatal bar and a mandibular lingual arch using 0.051-in archwire were employed associated to a facial bow, anchored primarily with occipital pull and, after molar relationship correction, changed to high pull. RESULTS: Upper incisors presented a great amount of intrusion and some palatal root inclination as programmed in the treatment plan. The skeletal mandibular response was favorable to achieve profile balance. Periapical radiograph showed rounded apex of incisor roots, expected in any orthodontic intrusion movement. CONCLUSION: The clinical results present the successful approach to deep overbite malocclusion.